Polyethersulfone (PES) membranes for CO2/CH4 separation: Effect of polymer blending - Abdul Mannan, H. (Trans Tech Publications Ltd, 2014)
Effect of polymer blending on physico-chemical and gas permeation properties of polyethersulfone (PES) membrane was studied. PES was chosen as base polymer and polysulfone (PSF) and polyvinyl acetate (PVAc) were added as glassy and rubbery polymer additives respectively. The morphology, thermal stability and miscibility of PES membranes were characterized by FESEM, TGA and DSC respectively to observe the effect of polymer blending. The prepared membranes were tested for permeation of CO2 and CH4 at a feed pressure of 2 to 10 bar. PES-PSF membrane exhibits the separation properties identical to PES membrane. PES-PVAc blend membrane was found to be immiscible and high permeability was achieved while the selectivity was lost. Â© 2014 Trans Tech Publications, Switzerland.